1995
DOI: 10.1177/002204269502500103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Needle Exchange Using Street-Based Survey Methods

Abstract: This paper describes the demographic and drug use characteristics, and levels of HIV-related risk behavior, for a sample of injection drug users (N=50) participating in the San Francisco needle exchange program. Exchange patrons were recruited as they approached the street-based exchange program, and were interviewed immediately to minimize drop-out. Clients reported high levels of satisfaction with exchange services, and many reported decreasing HIV risk behavior since participating in the exchange. Regular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Wodak & Cooney identified 28 primary studies of IRB (needle/syringe borrowing, lending or re‐use); among these, there were 24 positive [41–43,45,50,54–56,60,61,64–77], one negative [51], one indeterminate result [78] and two showing no association [48,79]. [Wodak & Cooney cited 29 studies, but one of these (Gibson, D. R. & Flynn, N. M. (2001) AIDS Research Institute, University of California, San Francisco), is not a primary research study.]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wodak & Cooney identified 28 primary studies of IRB (needle/syringe borrowing, lending or re‐use); among these, there were 24 positive [41–43,45,50,54–56,60,61,64–77], one negative [51], one indeterminate result [78] and two showing no association [48,79]. [Wodak & Cooney cited 29 studies, but one of these (Gibson, D. R. & Flynn, N. M. (2001) AIDS Research Institute, University of California, San Francisco), is not a primary research study.]…”
Section: Resultsmentioning
confidence: 99%
“…The 23 studies [48,50,51,54–56,60,61,64–67,69–71,74–79] identified by Gibson et al. were covered by the other two core reviews, with the exception of Broadhead et al.…”
Section: Resultsmentioning
confidence: 99%
“…Questions were based on variables used in prior studies of SEP participants in San Francisco (Guydish et al, 1998;Guydish et al, 1995) with additional variables of interest submitted by an all-female community advisory board. The survey was pre-tested with 5 female IDU using the study procedures described above.…”
Section: Methodsmentioning
confidence: 99%
“…Twelve investigations were initiated elsewhere, including Canada, the Netherlands, the United Kingdom, Switzerland, Sweden, Nepal, Russia, and Puerto Rico. The 31 studies had a total, cumulative N of 52,678, ranging from 49 (Guydish and Clark, 1995) to 35,460 (Hagan et al, 1991). Discounting the latter, mean number of subjects per study was 574.…”
Section: Descriptive Datamentioning
confidence: 99%